Exploring Another Piece of the Puzzle: Comorbid Mental Health Challenges in Children with Autism Spectrum Disorder - Kansal, Nisha; Kim, Samuel Seunghon (The Meducator, 2016)
Autism spectrum disorder (ASD) is characterized by impairments in social communication and restricted, repetitive behavioural patterns.1 In the United States, the prevalence of ASD is estimated to be 1 in 68 children.2 As children with ASD enter adolescence, they face difficulties brought on not only by the core functional impairments of their primary disorder but also by common psychiatric comorbidities, such as depression and anxiety. The prevalence estimates of these comorbidities vary widely, which may be explained by differences in assessment tools used between epidemiological studies. In this review, the most commonly used assessment tools for comorbidities among youth with ASD are presented. Out of the five tools identified, no tools had been specifically evaluated to measure anxiety among ASD youth, while only two tools had been evaluated to measure depression in this population. Across tools, there were numerous issues regarding psychometric properties, as well as differences in informants, leading to limitations when using these tools to measure comorbid psychiatric concerns in youth with ASD. Future research should aim to design better assessment tools to strengthen the quality of research in this field and better inform resource allocation and clinical practice.